'This wound has spoilt everything': emotional capital and the experience of surgical site infections. Issue 8 (November 2014) - Brown, Brian; Tanner, Judith; Padley, Wendy
Abstract In this article we explore the experience of suffering from a surgical site infection, a common complication of surgery affecting around 5 per cent of surgical patients, via an interview study of 17 patients in the Midlands in the UK. Despite their prevalence, the experience of surgical site infections has received little attention so far. In spite of the impairment resulting from these iatrogenic problems, participants expressed considerable stoicism and we interpret this via the notion of emotional capital. This idea derives from the work of Pierre Bourdieu, Helga Nowotny and Diane Reay and helps us conceptualise the emotional resources accumulated and expended in managing illness and in gaining the most from healthcare services. Participants were frequently at pains not to blame healthcare personnel or hospitals, often discounting the infection's severity, and attributing it to chance, to 'germs' or to their own failure to buy and apply wound care products. The participants' stoicism was thus partly afforded by their refusal to blame healthcare institutions or personnel. Where anger was described, this was either defused or expressed on behalf of another person. Emotional capital is associated with deflecting the possibility of complaint and sustaining a deferential and grateful position in relation to the healthcare system.